Hubungan Intensitas Pembelajaran Pendidikan Agama Islam dengan Penurunan Perilaku Bullying di SMP Islam Amanah Ummah - Ismail Hasan; Muhammad Ja’far Nashir (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to examine the relationship between the intensity of Islamic Religious Education (PAI) learning and the reduction of bullying behavior at Amanah Ummah Islamic Junior High School. Bullying among teenagers is a serious issue that requires attention in order to create a safe and comfortable learning environment. PAI learning is expected to have a positive impact on students’ social behavior, particularly in reducing bullying. This research uses a quantitative approach with a correlational design, involving 187 students as the sample. Data were collected through questionnaires measuring the intensity of PAI learning and levels of bullying behavior. Pearson correlation analysis showed a significant relationship: the higher the intensity of PAI learning, the lower the incidence of bullying. These findings highlight the importance of effective PAI instruction in shaping students' character and fostering a bullying-free school environment.